Advancements of hot-melt extrusion technology to address unmet patient needs and pharmaceutical quality aspects - Park, Chulhun; Renuka, Vanamane S.; Lee, Beom Jin; de la Peña, Ike; Park, Jun Bom (Journal of Pharmaceutical Investigation, 2024)
Background: Hot-melt extrusion (HME) significantly affects pharmaceutical manufacturing by enhancing drug solubility and bioavailability. Advancements in HME technology to produce FDA-approved drugs have highlighted its reliability and innovative potential in the pharmaceutical industry. Optimization of the processing parameters of HME-based drug products is aligned with the importance of high-quality drug production through an advanced manufacturing system. Area covered: This review covers the advancements in HME technology, focusing on pharmaceutical quality aspects and addressing unmet patient needs. Additionally, this review addresses the benefits of continuous manufacturing advancements for drug product quality and the importance of process analytical technology (PAT) tools. These tools are essential for monitoring product quality and consistency, maintaining the traceability of raw materials, and ensuring quality control during continuous pharmaceutical manufacturing. Expert opinion: The ongoing evolution of HME technology is a significant step towards creating more efficient and patient-focused drug products. Advances in processing parameters and PAT tools not only improve the quality and effectiveness of HME-based drug products but also satisfy unmet patient needs. The future of HME technology appears promising, with the potential to further refine drug delivery mechanisms and address both current and future unmet needs in pharmaceutical care.
Keywords: Continuous pharmaceutical manufacturing; Hot-melt extrusion; Patient-focused drug development; Quality-by-design; Residence time distribution; Unmet patient needs